On the application of boundary layer control to a slender wing supersonic airliner cruising at M = 2.2 - Craven, A. H.; Hopkins, H. L. (College of Aeronautics, 1962)
The use of suction or injection to reduce the drag of a supersonic airliner is considered. It is shown that injection gives no reduction in operating costs. With suction applied to an M =2.2 aircraft on the London - New York route, the basic operating cost of 13.30d per short ton statute mile is expected to be reduced by 0.5d for the same payload assuming no change in configuration. If the theoretical maximum skin friction reduction could be obtained the payload could be increased by 4750 lb. and the direct operating cost could be reduced to 10.63d per short ton statute mile.